2004
DOI: 10.1007/s11284-004-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Edge effects in a tropical montane forest mosaic: experimental tests of post‐dispersal acorn removal

Abstract: Forest edges created by scattered-patch clearcutting have become common in tropical montane cloud forests in the highlands of Chiapas, Mexico. It was hypothesised that forest edges may influence regeneration of oak species, which are canopy dominants in these forests, by affecting the activities of small mammal species. Acorns of different oak species varying in germination timing were offered to predators and/or dispersers at different positions along replicated forest edges during 2 consecutive years. We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 63 publications
2
31
0
2
Order By: Relevance
“…Yet, the effects of fragmentation on these forests are not well understood. Few studies on forest edges have been conducted in montane areas [e.g., [22][23][24][25] and, to our knowledge, none has tried to separate the effects of both forest edges and canopy openness on tree communities (but see the study by Restrepo and Vargas [26] on the effects of anthropogenic edges and treefall gaps on two understory shrubs in a neotropical montane forest). In this study, we analyze forest structure and composition along the edge-interior gradient in a tropical montane fragment to determine whether there is an interaction between gaps and edges.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the effects of fragmentation on these forests are not well understood. Few studies on forest edges have been conducted in montane areas [e.g., [22][23][24][25] and, to our knowledge, none has tried to separate the effects of both forest edges and canopy openness on tree communities (but see the study by Restrepo and Vargas [26] on the effects of anthropogenic edges and treefall gaps on two understory shrubs in a neotropical montane forest). In this study, we analyze forest structure and composition along the edge-interior gradient in a tropical montane fragment to determine whether there is an interaction between gaps and edges.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently with these distribution patterns of granivores, acorn removal rates gradually decreased from the forest interior towards the forest edge and, for most oak species, they abruptly decreased in the clearing. Previous studies have reported that seed removal rates in HMF decrease from the interior of forests towards human-impacted areas (Sork 1983, Webb & Willson 1985, McCormick & Meiners 2000, López-Barrera et al 2005, Bustamante et al 2012), but richness and abundance of seed consumers have been barely considered to explain seed removal patterns. In this study, acorn removal rates correlated with these two variables (richness and abundance of granivores) and their values decreased from the maximum distance inwards the forest (50 m) towards the maximum distance in the man-made clearing (-50 m).…”
Section: Discussionmentioning
confidence: 99%
“…Further, several studies have assessed how increasing distance to edges affects seed removal by vertebrates, but their results are not fully consistent. Some authors have reported increased seed removal rates inwards the forest (Sork 1983, Bustamante et al 2012, while others found higher removal rates at forest edges (Donoso et al 2003, Kollmann & Buschor 2003, López-Barrera et al 2005 or even in man-made clearings (Díaz et al 1999). These discrepancies have been attributed to the chemical composition of seeds, as highly palatable seeds are quickly removed irrespectively of the habitat they are located, or differences in seed size, as bigger seeds are only removed by large granivores visiting the different habitats in the HMF (Donoso et al 2003, Bustamante et al 2012, ReyBenayas et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…S. deppei and S. aureogaster both feed upon fungi, acorns, pine nuts, berries, fruits, needles, and leaves (Musser 1968;Estrada and Coates-Estrada 1985;López-Barrera et al 2005). The mantled howler monkey (Alouatta palliata), Geoffroy's spider monkey (Ateles geoffroyi), kinkajou (Potos flavus), cacomistle (Bassariscus sumichrasti), Mexican hairy dwarf porcupine (Coendou mexicanus), common opossum (Didelphis marsupialis), deer mice (Peromyscus), and gray four-eyed opossum (Philander opossum) also have some dietary overlap with S. aureogaster (Estrada and Coates-Estrada 1985;López-Barrera et al 2005). In Florida, the white-crowned pigeon (Patagioenas leucocephala), listed as a threatened species in Florida (Florida Fish and Wildlife Conservation Commission 2011) and "Near Threatened" by the International Union for…”
Section: Ecologymentioning
confidence: 99%